A Review of the Evolution of Research on Proposals for Bamboo Culms Connections in Structural Systems - Gaffuri, Bruna A.; Moura, Jorge D. M.; Barbosa, Juliana C. [UNESP]; de Medeiros, Marcelo H. F.; Gobbi, Andressa; Silva, Ricardo D. (BioResources, 2023)
Structural systems built from raw bamboo have been used for years due to its highly renewable characteristics, versatility, and abundance in various countries, e.g., China, Indonesia, all over South America, and especially Brazil. It is also considered a low specific weight material, which means it is easy to handle and transport. These characteristics make it a low-cost material for building construction. The objective of this systematic bibliometric review is to identify innovations in bamboo culms structural connections in order to contribute to the advancement of technology applied to civil construction by seeking joints that consider the use of industrialized or standardized products. This review revealed there is still no ideal connection capable of solving the great problem of this subject, which points out the need for more studies on the topic. This investigation also allows for the classification of the connections into 5 categories: Bolted connections; Steel member and Steel plate connections; Reinforced Connections with filler; Parameterized connections, and; Connections with the use of wooden dowels.
Keywords: Bamboo; Connections; Culms; Joints; Parametric design; Raw bamboo; Steel connections